2011
DOI: 10.1016/j.bbapap.2010.10.012
|View full text |Cite
|
Sign up to set email alerts
|

An introduction to NMR-based approaches for measuring protein dynamics

Abstract: Proteins are inherently flexible at ambient temperature. At equilibrium, they are characterized by a set of conformations that undergo continuous exchange within a hierarchy of spatial and temporal scales ranging from nanometers to micrometers and femtoseconds to hours. Dynamic properties of proteins are essential for describing the structural bases of their biological functions including catalysis, binding, regulation and cellular structure. Nuclear magnetic resonance (NMR) spectroscopy represents a powerful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
506
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 471 publications
(526 citation statements)
references
References 202 publications
(270 reference statements)
14
506
0
6
Order By: Relevance
“…It is natural that allosteric regulation depends on modulation of protein motions, because substrate binding and catalysis are linked to conformational dynamics (19,20). Unlike static X-ray structures, solution NMR relaxation dispersion techniques have been instrumental in providing high-resolution conformational exchange information using sitespecific isotope labeling (21). In NMR studies of CypA, a dynamic continuum has been identified such that the relaxation profiles cannot be globally fit to one or two exchange phenomena and are instead indicative of more localized motions (22).…”
mentioning
confidence: 99%
“…It is natural that allosteric regulation depends on modulation of protein motions, because substrate binding and catalysis are linked to conformational dynamics (19,20). Unlike static X-ray structures, solution NMR relaxation dispersion techniques have been instrumental in providing high-resolution conformational exchange information using sitespecific isotope labeling (21). In NMR studies of CypA, a dynamic continuum has been identified such that the relaxation profiles cannot be globally fit to one or two exchange phenomena and are instead indicative of more localized motions (22).…”
mentioning
confidence: 99%
“…1, E and F) and/or by partially stabilizing additional states, distinct from the fully active or fully inactive states, in which the activation function of the CBD is compromised. To test these hypotheses, here we comparatively analyze the S672R and WT HCN4 CBDs in both apo-and holo-forms using NMR spectroscopy, which reports on dynamics at residue resolution and over multiple time scales (30,39). Furthermore, we examined the S672R versus WT relaxation and chemical shift changes, which are exquisitely sensitive atomic reporters of subtle but functionally relevant allosteric perturbations that are often elusive to other structural techniques (27,30).…”
mentioning
confidence: 99%
“…More importantly, residues in the phosphoacceptor region, as well as helices H0 and H5, showed substantially greater intensity changes yet no chemical shift perturbations. This suggests that these residues undergo pronounced exchange broadening 30 owing either to direct contacts with the kinase, as would be expected for the phosphoacceptors, or to indirect conformational perturbations. Indeed, when mapped on a homology model of PntP2 142-252 , the residues in helices H0 and H5 are both in close proximity and adjacent to side chains in the PNT domain shown previously by mutagenesis to be involved in docking interactions with the ERK2 Rolled [ Fig.…”
Section: Map Kinase Docking By Pointed-p2mentioning
confidence: 96%
“…However, it is difficult to estimate the nature of the conformations sampled by these fast motions from 15 N relaxation measurements alone. 30 More importantly, rapid amide HX was detected for residues throughout helices H0/H1 [ Fig. 4(A)].…”
Section: Pointed-p2 Pnt Domain Contains a Dynamic Helix H0mentioning
confidence: 99%